The Challenges of Healthy Lifestyle: A Study Case of Kentucky Fried Chicken - Chia Yi Chan; Daisy Mui Hung Kee; En Chong; Kim Kim Hak; Pei Hung Aw Yeong; Stephani Stephani; Hani Sara; Bhardhwaj Chanchal; Majdi Anwar Quttainah; Rudresh Pandey; Liem Gai Sin (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
Living a healthy lifestyle is being aware of by our society. Most of the people nowadays will change their eating habits as one of the ways to help them to build a healthy body. As we know, many people are suffered from different types of diseases and the common ones are diabetes, high blood pressure, high cholesterol. KFC contains tens-fat that is harming consumer's health. Their unethical behavior has influenced widely against their customers. It is a serious ethical dilemma that can be found in KFC. The health problems connected to poor diets are well understood too, so there is a consensus that our response to this problem is to improve public awareness of relevant risks and behaviors and the redesign of these damaging food environments. Kentucky Fried Chicken (KFC) is an American fast-food restaurant and the second-largest restaurant chain in the world. Being specialized in fried chicken, KFC is facing a great challenge in this generation which focuses on a healthy lifestyle. The result of this paper will show the changes and improvements that can help KFC to face this challenge.